Spatial and temporal groundwater biogeochemical variability help inform subsurface connectivity within a high-altitude Alpine catchment (Riale di Ronco, Switzerland) - Acciardo, Andrew S.; Arnet, Moira; Gholizadeh Doonechaly, Nima; Ceccato, Alberto; Rodriguez, Paula; Tran, Hoang N.H.; Wenning, Quinn; Zimmerman, Eric; Hertrich, Marian; Brixel, Bernard; Magnabosco, Cara (Frontiers in Microbiology, 2025)
Accessing the deep terrestrial subsurface (greater than 1 km below the surface) presents significant practical challenges, leaving these ecosystems largely uncharacterized despite their extensive presence beneath Earth's landmasses. In this study, we introduce the BedrettoLab Deep Life Observatory (DELOS), a new underground laboratory to study the biogeochemical diversity of groundwater in a high-altitude Alpine catchment tens of meters to 1.6 km underground. Biogeochemical monitoring of DELOS over spatial and temporal scales highlight three dominant ecotypes throughout DELOS: (1) Shallow groundwater with low electrical conductivity enriched in Leptospirillia; (2) High-inflow fault zones enriched in ultra-small bacteria and archaea; (3) Bicarbonate-enriched waters that are enriched in Candidatus Kryptonia and Spirochaetota. Despite a consistent lithology throughout DELOS, groundwater from fractures that are spatially near each other are not always represented by the same ecotype and can be more similar to groundwater emitted from fractures thousands of meters away. Despite this heterogeneity, the biological and hydrochemical compositions of the groundwater of individual fractures remained relatively stable throughout the course of a 1-year monitoring period. An exception to this trend occurred after a series of seismic events near one groundwater-bearing fracture. Here, the microbial community and hydrochemical composition of the groundwater changed after the seismic events but returned to the site's “baseline” composition within 3 weeks. Taken together, these findings provide new insights into the spatial and temporal heterogeneity of deep subsurface ecosystems and the subsurface connectivity of an Alpine subsurface environment.